EVALUASI KEBERADAAN ZONA SELAMAT SEKOLAH DI KECAMATAN PONTIANAK KOTA - Larasasti, Fajiarsih; Syafaruddin, -; Azwansyah, Heri Azwansyah (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2018)
A lot of school in big cities located on the edge of highway where there’s a lot of vehicle passing by at high speed. School Safe Zone (SSZ) is a control of traffic activity trough the management of speed and marks and signs placement on road side of school’s zone purposed to prevent accidents as an effort to ensure child safety at school (Director General of Land Transportation, 2014). The purpose of this research is to know how the exsistance of School Safe Zone on Pontianak City disctrict, to know whether the School Safe Zone is in accordance with the standart of the related institute, to analyze the characteristic of accidents that happened on the reviewed location and to determined the improvement strategy program of SSZ from school located on Pontiank City district such as Elementry School 34, SMK N 1. Conclusions obtained from the reserch is there are marks and signs in several school that didn’t met standart. Accidents are grouped based on time, type, and victims from 2012 to 2016. The highest accident happened on 2013 from every accident group. Improvement strategies in locations are installation of marks and sings that is not available on locations, re-applying fading paint, and the distance placement of signs are adjusted based on the problem on field.Keywords: Evaluation, School Safe Zone, accident, improvement strategy.